2013
DOI: 10.1186/1755-7682-6-20
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction in a Moroccan emergency department

Abstract: BackgroundMeasuring healthcare quality and improving patient satisfaction have become increasingly prevalent, especially among healthcare providers and purchasers of healthcare. Currently, research is interested to the satisfaction in several areas, and in various cultures. The aim of this study was; to confirm the reliability and validity of the Arabic version of the Emergency Department Quality Study (EDQS), to evaluate patient satisfaction with emergency care, and to determine associated factors with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 18 publications
6
25
4
Order By: Relevance
“…Nonetheless, there was no relationship reported by age, gender, work shifts, severity of the patient conditions, and patients who completed the questionnaire. This finding is not in line with the study of Damghi et al that observed an association between satisfaction and type of emergency admission, waiting time and the distance from patient's home to the hospital (21). Further analysis of data revealed that patients who arrived in the ED between 14:00 to 20:00 were more dissatisfied than those who arrived in the other times of the day and the difference between arriving time and satisfaction level did not reach a significant level.…”
Section: Discussioncontrasting
confidence: 96%
“…Nonetheless, there was no relationship reported by age, gender, work shifts, severity of the patient conditions, and patients who completed the questionnaire. This finding is not in line with the study of Damghi et al that observed an association between satisfaction and type of emergency admission, waiting time and the distance from patient's home to the hospital (21). Further analysis of data revealed that patients who arrived in the ED between 14:00 to 20:00 were more dissatisfied than those who arrived in the other times of the day and the difference between arriving time and satisfaction level did not reach a significant level.…”
Section: Discussioncontrasting
confidence: 96%
“…This is consistent with other studies which showed that "Emergent" and "Urgent" patients perceived their throughput times more favorably than non-urgent patients [23]. The patients with high acuity tends to be more satisfied as shown in our study with their ED care because of their less waiting time and more attention from ED providers [30,31].…”
Section: Discussionsupporting
confidence: 82%
“…Eventhough it is a difficult to adopt the results of foreign studies into the Moroccan context, the results of our study was better or similar to others moroccan studies [13][14][15][16] or countries sharing similar socio-economic levels [17][18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 80%